2005
DOI: 10.1002/acp.1069
|View full text |Cite
|
Sign up to set email alerts
|

The facilitating effect of verbalization on the recognition memory of incidentally learned faces

Abstract: The purpose of this study was to test the hypothesis that requiring people to verbally describe a target face from memory facilitates their subsequent recognition when their memory for the target is poor and interferes with recognition when such memory is strong. In Experiment 1, a target face was presented to participants for 30 s or 100 s under a nominal task instruction, and they incidentally familiarized themselves with it. Verbalization increased the rate of correct recognition only when the target was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…This is in contrast to previous studies that have found a negative effect of verbalisation on recognition memory (verbal overshadowing). Itoh [47] found that verbalisation interferes with subsequent face recognition when memory for the target person is good, whereas verbalisation enhances recognition when memory is poor. So, the findings of the current experiment could be due to poor recognition memory for the stimuli at encoding, which can be seen in the low accuracy scores for pictures that were imagined only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to previous studies that have found a negative effect of verbalisation on recognition memory (verbal overshadowing). Itoh [47] found that verbalisation interferes with subsequent face recognition when memory for the target person is good, whereas verbalisation enhances recognition when memory is poor. So, the findings of the current experiment could be due to poor recognition memory for the stimuli at encoding, which can be seen in the low accuracy scores for pictures that were imagined only.…”
Section: Discussionmentioning
confidence: 99%
“…This second representation then leads to recoding interference or source confusion, thereby decreasing recognition accuracy. However, if the initial representation of the visual stimulus is itself coarse and lacking in detail [47] or if the verbal description is itself sufficient in discriminating between target and distracter items [40,45], the verbal overshadowing effect disappears or even reverses, and improved recognition is observed under conditions of verbalisation [48].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This allowed manipulation of whether the verbally described features were distinguishing (modifi ed) features between target and distractors. A single target face was used because most verbal overshadowing studies use one test set ( Finger & Pezdek, 1999 ;Finger, 2002 ;Kitagami, et al ., 2002 ;Itoh, 2005 ). All stimuli were presented in gray scale.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, although participants' attention may have been directed to featural information, describing salient features may have reduced the detrimental eff ect of this processing shift on recognition performance by directing participants' attention to the salient features. Verbal enhancement eff ects on face recognition have been reported ( Winograd, 1981 ;Brown & Lloyd-Jones, 2005 ;Jones, et al ., 2013 ); however, participants in those studies verbalized information about targets in an encoding phase or immediately after target presentation (but see Itoh, 2005 ). The eff ect of verbalization may diff er depending on the timing.…”
mentioning
confidence: 99%